Different aggregation states of a nuclear localization signal‐tagged 25‐kDa C‐terminal fragment of TAR RNA/DNA‐binding protein 43 kDa. (12th May 2017) - Kitamura, Akira; Yuno, Sachiko; Muto, Hideki; Kinjo, Masataka
Abstract : The mechanism and cause of motor neuronal cell death in amyotrophic lateral sclerosis (ALS), a devastating neurodegenerative disorder, are unknown; gain of function of oligomers and aggregation of misfolded proteins, including carboxyl‐terminal fragments (CTFs) of TAR RNA/DNA‐binding protein 43 kDa (TDP‐43), have been proposed as important causative factors in the onset of ALS. We recently reported that a nuclear localization signal (NLS)‐tagged 25‐kDa CTF of TDP‐43 (TDP25) could decrease the cell‐death proportion compared with that promoted by TDP25. Here, we show oligomeric states of NLS‐TDP25 and its detailed localization property using super‐resolution fluorescence microscopy, FRET, fluorescence recovery after photobleaching, and fluorescence correlation spectroscopy analysis. NLS‐TDP25 efficiently formed a nucleolar cap structure via RNA binding in the presence of actinomycin D, but TDP25 did not. Although cytoplasmic inclusion bodies including TDP25 had a disordered and immobile structure, NLS‐TDP25 in the nucleolus was ordered and dynamic. In the diffuse state, TDP25 formed fewer oligomers and interacted with the molecular chaperone, HSP70; however, NLS‐TDP25 formed oligomers. These results suggested that NLS‐tagged TDP25 can change its structure to use ordered oligomeric but nontoxic state. Moreover, the structure of ordered oligomers as well as nuclear sequestration may be important in mediating cytotoxicity in ALS pathology. Abstract : TDP25 aggregate formation is protected by interactions with RNA (green). The NLS tag binds to nucleolar RNA (orange). Intermolecular assembly of NLS‐TDP25 via nucleolar RNA may form differently ordered oligomers (bottom left). In contrast, TDP25 lacking complexed RNA immediately forms cytoplasmic aggregates (bottom right).